2005
DOI: 10.1350/ijps.7.2.123.65772
|View full text |Cite
|
Sign up to set email alerts
|

Shopping Centre Design, Decline and Crime

Abstract: It is now widely accepted that the design of buildings and their surroundings can influence the commission of crime and nuisance behaviour (Garrad, 1999) and that the proper design and effective use of the built environment can lead to a reduction in the fear and incidence of crime, and an improvement in the quality of life (Skogan, 1990a). This article reports on research undertaken to determine whether architects, designing shopping centres in the 1960s and late 1990s, were aware of the link between environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 3 publications
4
17
0
Order By: Relevance
“…Visitors' perceptions of a shopping centre's safety is a function of a number of overlapping factors such as the characteristics of the customers themselves, the safety conditions of the facility, the quality and maintenance of the shopping mall environment and surrounding areas, and the security system in place (Poyser, 2004;Sandberg, 2016;Savard & Kennedy, 2014). The international literature is populated by examples showing how individual factors affect declared perceived safety; the most common of which include age, gender, place of residence, frequency of use of the place, and previous crime victimisation (Ceccato, 2014;Hale, 1996;Pain, 2000;Skogan & Maxfield, 1981).…”
Section: Theoretical Background Perceived Safety In Shopping Centresmentioning
confidence: 99%
See 3 more Smart Citations
“…Visitors' perceptions of a shopping centre's safety is a function of a number of overlapping factors such as the characteristics of the customers themselves, the safety conditions of the facility, the quality and maintenance of the shopping mall environment and surrounding areas, and the security system in place (Poyser, 2004;Sandberg, 2016;Savard & Kennedy, 2014). The international literature is populated by examples showing how individual factors affect declared perceived safety; the most common of which include age, gender, place of residence, frequency of use of the place, and previous crime victimisation (Ceccato, 2014;Hale, 1996;Pain, 2000;Skogan & Maxfield, 1981).…”
Section: Theoretical Background Perceived Safety In Shopping Centresmentioning
confidence: 99%
“…Poyser (2004) reports on research undertaken to assess whether architects were aware of the link between environmental design and crime when they built shopping centres in the 1960s up to 1990s (the study is a comparison of two English shopping centres). Poyser (2004) found that some architects were more aware than others of the links between the built environment and fear of crime in shopping centres. Moreover, he found that ongoing maintenance and cleanliness of the built environment were signs of control that reassured users.…”
Section: Shopping Centre Environment and Perceived Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…How much they are exposed to crime depends on their location in the mall but also internal and external features such as good lighting, design and positions of doors, windows and stair cases, entrances. These features may reduce the possibility of crime occurring by stimulating surveillance, fostering territoriality and reducing areas of conflict by controlling access from outsiders (Ekblom, 1995(Ekblom, , 2011(Ekblom, , 2013Jeffery, 1977;Newman, 1972;Poyser, 2004).…”
Section: Crime In Shopping Centres: a Conceptual Modelmentioning
confidence: 99%